Analisis Komponen Daya Tarik Wisata di Desa Wisata Pentingsari, Kelurahan Umbulharjo, Kecamatan Cangkringan, Kabupaten Sleman, DIY - , BAHTIAR SAIFUL HIDAYAT ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study discusses the analysis component of tourist attraction in Pentingsari Tourism Village, Yogyakarta. This study is to determine the components of tourist attraction in Pentingsari Tourism Village given independent status as a tourism village but has different natural potencies compared to the common tourism villages identically known with its sceneries, rice fields, and rivers. The method is using the rating according to several components of touristâs perspective. The rating is done by randomly distributing questionnaires and interviewing several figures represented the informations. The result of this study is a form table of analytical tourist attraction components.